The university campus: an engine for livability - Chmiel, Benjamin (Kansas State University, 2014)
What makes a city a place people love and want to live is the essence of livability. Livable cities are places where people can delight in a high quality of life. College towns are great places to live because their universities function as a cultural wealth and an economic anchor for the city. Using Manhattan, KS and Kansas State University (KSU) as a case study, this study utilizes a survey as an instrument to investigate the possible correlations and patterns between the perceived quality of life of permanent residents of college towns and their degree of interaction with their university’s campus. Using statistical analyses of this data, this study explores the relationships between a higher quality of life in Manhattan and a higher interaction with KSU. As well, it seeks to find what aspects of university interaction have the most impact on quality of life, if there are any shortfalls in quality of life in Manhattan, and if the university can play a role in the strategy to mitigate for these shortfalls. In this, town-gown relationships give insight to creating more livable cities as a whole.
Keywords: College town; Livability; Quality of life; Relationships; Town-gown University; Urban Planning (0999)